Reindeer in the USSR: problems of protection and rational use - E. E. Syroechkovski (Rangifer, 2010)
There are approximately 2.2 million domestic and 1 million wild reindeer in the USSR today. It is unlikely that the number of domestic reindeer will increase further but there is a tendency for further growth in several large populations of wild reindeer. All middle-sized and small populations of wild reindeer need protection. During the whole initial period of penetration and adaptation of man to the north, the life of ancient inhabitants was closely linked to hunting wild reindeer. Neolithic relics of North Eurasia witness the wide distribution of a relatively monotonous Stone Age reindeer hunting culture. Domestication of reindeer began not less than a thousand years ago. Large-scale reindeer husbandry developed only 300-400 years ago and prospered for about 200 years. Social changes impeded its development after the 1950s, resulting in the restoration of wild riendeer herds.